Social Mobility of The Bugis Female Hajj Pilgrims - Muhammadiyah, Hilmi; Haji Ahmad, Siti Sara binti (Al-Albab, 2024)
This research delves into the social mobility of Bugis female Hajj pilgrims, examining not only the ways in which the experience of performing the Hajj transforms Bugis women socially but also how this mobility becomes integral to their cultural lives. Utilizing qualitative methods which include field studies and interviews with Bugis women who have completed the Hajj, this research positions them as agents, actors, and subjects. Its objective is to reveal the various forms of social mobility that have reshaped the status of Bugis women who have performed the Hajj. Specifically, it investigates the role of the Hajj as a social identity within Bugis society, the social and cultural transformations experienced by Bugis female Hajj pilgrims, and the effects of their social mobility on changes in their societal status and roles. Field findings show that the social mobility of Bugis female Hajj pilgrims is deeply intertwined with the community’s respect for the difficult journey of performing the Hajj, from departure to return. This journey redefines women’s positions within religious rituals, fosters cultural cohesion through the symbolic attributes worn during the Hajj, and generates both direct and indirect impacts on society through the pilgrims’ contributions.